Health Maintenance Consensus for Adults With Inflammatory Bowel Disease. Issue 10 (19th July 2021) - Syal, Gaurav; Serrano, Mariastella; Jain, Animesh; Cohen, Benjamin L; Rieder, Florian; Stone, Christian; Abraham, Bincy; Hudesman, David; Malter, Lisa; McCabe, Robert; Holubar, Stefan; Afzali, Anita; et al.
Abstract: Background: With the management of inflammatory bowel disease (IBD) becoming increasingly complex, incorporating preventive care health maintenance measures can be challenging. The aim of developing these updated recommendations is to provide more specific details to facilitate their use into a busy clinical practice setting. Method: Fifteen statements were formulated with recommendations regarding the target, timing, and frequency of the health maintenance interventions in patients with IBD. We used a modified Delphi method and a literature review to establish a consensus among the panel of experts. The appropriateness of each health maintenance statement was rated on a scale of 1 to 5 (1–2 as inappropriate, and 4–5 as appropriate) by each panelist. Interventions were considered appropriate, and statements were accepted if ≥80% of the panelists agreed with a score ≥4. Results: The panel approved 15 health maintenance recommendations for adults with IBD based on the current literature and expert opinion. These recommendations include explicit details regarding specific screening tools, timing of screening, and vaccinations for adults with IBD. Conclusions: Patients with IBD are at an increased risk for infections, malignancies, and other comorbidities. Given the complexity of caring for patients with IBD, this focused list of recommendations can be easily incorporated in to clinical care to help eliminate the gap in preventative care for patients with IBD.